1989
DOI: 10.1017/ccol0521266165
|View full text |Cite
|
Sign up to set email alerts
|

Misspecification Tests in Econometrics

Abstract: Misspecification tests play an important role in detecting unreliable and inadequate economic models. This book brings together many results from the growing literature in econometrics on misspecification testing. It provides theoretical analyses and convenient methods for application. The main emphasis is on the Lagrange multiplier principle, which provides considerable unification, although several other approaches are also considered. The author also examines general checks for model adequacy that do not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(114 citation statements)
references
References 0 publications
0
114
0
Order By: Relevance
“…Autocorrelation occurs when the residuals are not independent from each other and not linearly auto-correlated (Cohen et al, 2013). If this assumption does not occur, there is a correlation between the error terms of independent variables, and it can weaken the estimates (Godfrey, 1988). The Durbin-Watson and Breusch-Godfrey LM tests are usually the preferred tests to examine this assumption.…”
Section: Preliminary Analysesmentioning
confidence: 99%
“…Autocorrelation occurs when the residuals are not independent from each other and not linearly auto-correlated (Cohen et al, 2013). If this assumption does not occur, there is a correlation between the error terms of independent variables, and it can weaken the estimates (Godfrey, 1988). The Durbin-Watson and Breusch-Godfrey LM tests are usually the preferred tests to examine this assumption.…”
Section: Preliminary Analysesmentioning
confidence: 99%
“…Both subsystems are estimated including two lags 5 and a constant restricted to the cointegration space 6 . Multivariate tests for autocorrelation (Godfrey, 1988) and normality (Doornik and Hansen, 1994) have been carried out to check for model statistical adequacy before applying the reduced rank tests. Results indicated that both subsystems could be considered correctly specified 7 .…”
Section: Model Specification and Cointegration Rankmentioning
confidence: 99%
“…The test described in Jalan and Ravallion (2002) (following Godfrey, 1988) is used to test the null hypothesis that 1 = t r for all t. In estimating equation (4) The essential condition to justify this choice of instruments is that the error term in (4) is second-order serially independent, as implied by serial independence of it µ . The Arellano and Bond (1991) second-order serial correlation test is performed, given that the consistency of the estimator for the quasi-differenced model depends on the assumption that the composite error term is second-order serially independent.…”
Section: Econometric Modelmentioning
confidence: 99%